2007
DOI: 10.1002/jhet.5570440626
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti‐staphylococcal activity of new halogenated pyrroles related to Pyrrolomycins F

Abstract: The chemical synthesis of new halogenated pyrroles related to pyrrolomycins F is described and the anti-staphylococcal activity compared. The replacement of 4'-bromo atom of parent compounds with two chloro atoms at 3' and 5' position increase the antibacterial activity against a reference strain of S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Recently, Dubois et al described a clinical strain of E. coli producing OXA-30 (now known to be identical to OXA-1) with decreased susceptibility (MIC = 4 mg/L) but not highlevel resistance to cefepime [5,6]. Like us, they were unable to demonstrate any outer membrane porin deficiency in their strain.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, Dubois et al described a clinical strain of E. coli producing OXA-30 (now known to be identical to OXA-1) with decreased susceptibility (MIC = 4 mg/L) but not highlevel resistance to cefepime [5,6]. Like us, they were unable to demonstrate any outer membrane porin deficiency in their strain.…”
mentioning
confidence: 71%
“…1), synthesised and characterised by us [6] and related to pyrrolomycins B-E, were potential agents with improved antibacterial and antibiofilm activity against a panel of Gram-positive and staphylococcal biofilms.…”
mentioning
confidence: 99%
“…The structural changes generated compounds with less antimicrobial activity with respect to compound 4; nevertheless, compounds 18a,b and 19a,b resulted more active on S. aureus than the comparator amikacin, as shown in Table 8. Moreover, the Authors reported the synthesis of new halogenated pyrroles related to pyrrolomycins F 20a-e to investigate their anti-Gram-positive and anti-staphylococcal activities and their ability to inhibit the formation of biofilms (Figure 7) [39,40,53]. Moreover, the Authors reported the synthesis of new halogenated pyrroles related to pyrrolomycins F 20a-e to investigate their anti-Gram-positive and anti-staphylococcal activities and their ability to inhibit the formation of biofilms (Figure 7) [39,40,53].…”
Section: Synthetic Pyrrolomycinsmentioning
confidence: 99%
“…Moreover, the Authors reported the synthesis of new halogenated pyrroles related to pyrrolomycins F 20a-e to investigate their anti-Gram-positive and anti-staphylococcal activities and their ability to inhibit the formation of biofilms (Figure 7) [39,40,53]. Moreover, the Authors reported the synthesis of new halogenated pyrroles related to pyrrolomycins F 20a-e to investigate their anti-Gram-positive and anti-staphylococcal activities and their ability to inhibit the formation of biofilms (Figure 7) [39,40,53]. (compounds 18a,b and 19a,b) to investigate whether the introduction of a keto or methylene spacer between the phenol and pyrroloyl moiety led to more active compounds [52].…”
Section: Synthetic Pyrrolomycinsmentioning
confidence: 99%
See 1 more Smart Citation